2012
DOI: 10.9735/0975-5276.4.6.263-265
|View full text |Cite
|
Sign up to set email alerts
|

MULTIDRUG RESISTANT Pantoea agglomerans IN A PATIENT WITH SEPTIC ARTHRITIS- A RARE REPORT FROM INDIA

Abstract: Introduction-Pantoea agglomerans (P. agglomerans)is gram negative bacterium that belongs to the family Enterobacteriaceae. It is an opportunistic pathogen in the immunocompromised, causing wound infections, bacteremia, and urinary tract infections. This species is currently listed as a Biosafety level 2 (BL2) organism due to clinical reports as an opportunistic human pathogen. Septic arthritis or synovitis is usually common, clinical manifestations caused by P. agglomerans and often correlated with a predispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The pattern of susceptibility and resistance exhibited in the present study may be due to prolonged and indiscriminate usage and prescription of particular antibiotics which often leads to possible resistance development in animals (Kwaga, 2012;Sharma, 2014). On table 3, questionnaires data analysis showed that 89(29.7%) milk samples were CMT positive of these; 13(4.3%) were contaminated with only yeasts, 7(2.3%) with only coliforms while, 24(8%) with yeasts and coliforms.…”
Section: Resultsmentioning
confidence: 84%
“…The pattern of susceptibility and resistance exhibited in the present study may be due to prolonged and indiscriminate usage and prescription of particular antibiotics which often leads to possible resistance development in animals (Kwaga, 2012;Sharma, 2014). On table 3, questionnaires data analysis showed that 89(29.7%) milk samples were CMT positive of these; 13(4.3%) were contaminated with only yeasts, 7(2.3%) with only coliforms while, 24(8%) with yeasts and coliforms.…”
Section: Resultsmentioning
confidence: 84%
“…Howsoever the mode of transmission is not always clear, but two main routes by which P. agglomerans can enter PIF are including (1) internal (intrinsic) contamination (e.g. through contaminated ingredients added after drying or from the processing environment following drying steps and before packaging), and (2) external (extrinsic) contamination of the PIF during reconstitution and handling.…”
Section: Discussionmentioning
confidence: 99%
“…Pantoea agglomerans (formerly Enterobacter agglomerans ) is a motile peritrichous, non-sporforming, Gram-negative aerobic bacilli in the Enterobacteriaceae family (1, 2). It is commonly found in the ecological niches such as water, soil, sewage, seeds, vegetables, feculent material and foodstuffs, as well as reported as both commercial and opportunistic pathogens of animals and humans (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 shows the pattern of resistance exhibited in the present study, this may be due to prolonged and indiscriminate usage and prescription of related antibiotics which often leads to possible resistance development in animals [21,22]. Overall, 53.8% of the isolates were multidrug resistant.…”
Section: Issn: 2789-3928mentioning
confidence: 82%